2006
DOI: 10.1557/proc-932-39.1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Swelling Bitumen – Host Formation: Scoping Calculations

Abstract: The Eurobitum bituminised waste product (BWP) from the former EUROCHEMIC reprocessing plant in Mol-Dessel (Belgium) contains a lot of salts, mainly NaNO 3 and CaSO 4 . In contact with pore water in an underground repository, the dehydrated salts in the BWP will rehydrate, resulting in swelling and, possibly, a swelling pressure build-up. A high swelling pressure might impede the integrity and the safety of the repository by creation of preferential pathways for radionuclide migration. In Belgium, the Boom Clay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In addition to the dissolution of NaNO 3 , anhydrous calcium sulfate ('natural anhydrite'; solubility $0.015 mol/L (M); density $2.96 g/ml) can recrystallise with 0.5 water molecules to 'Paris Plaster' (solubility $0.21 M; density $2.74 g/ml) or with two water molecules to gypsum (solubility $0.014 M; density $2.32 g/ml), also resulting in a volume and/or pressure increase. High swelling-induced deformation and stresses could thus lead to a mechanical disturbance and possibly damage of the surrounding host formation [17], of which the consequences in terms of barrier performance have to be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the dissolution of NaNO 3 , anhydrous calcium sulfate ('natural anhydrite'; solubility $0.015 mol/L (M); density $2.96 g/ml) can recrystallise with 0.5 water molecules to 'Paris Plaster' (solubility $0.21 M; density $2.74 g/ml) or with two water molecules to gypsum (solubility $0.014 M; density $2.32 g/ml), also resulting in a volume and/or pressure increase. High swelling-induced deformation and stresses could thus lead to a mechanical disturbance and possibly damage of the surrounding host formation [17], of which the consequences in terms of barrier performance have to be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The salts contained in the BW are important because they can affect the integrity of the Boom Clay through an osmosis-induced pressure caused by osmotic uptake of water by the waste (Li et al 2006;Valcke et al 2009). When water comes into contact with the BW the salt will dissolve and diffuse away.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the nearly constant volume tests demonstrate the importance of a well-reflected disposal design for the BW, to avoid high stresses on the Boom Clay. Preliminary scoping calculations have shown that there will be little or no damage to the clay if the radial stress exerted by swelling BW remains below $6.5 MPa 16 [37,38]. To avoid higher radial stresses, the number of drums per gallery cross-section should be limited.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%